(untitled) (Research, Society and Development, 2021)
Dental avulsion is the displacement of the tooth from its alveolus. Has a higher prevalence between 7 and 12 years. Dental replantation is the best approach for a good prognosis. Adequate management of teachers in schools is extremely important, however, in general, they do not perform properly due to lack of knowledge. Objective: Assess the level of knowledge, before and after training, of teachers from public and private schools about the correct management of dental avulsion. Material and Methods: This community-typed study was conducted with educators from public and private schools networs. A questionnaire was applied to 64 teachers from each network and, afterwards, their training was carried out. After a month, there was a reassessment of teachers already trained. The data were entered into the EXCEL spreadsheet and the program used to obtain statistical calculations was SPSS in version 23. Results: Only 3.1% of public school teachers and 15.6% of the private network had already received guidance on dentoalveolar trauma. In the first assessment, the question of where to take the student with an avulsed tooth showed a significant difference between the two groups of educators. Regarding the best way to store the tooth, only 5.5% chose “milk”, showing insufficient knowledge on the subject. After training, there was an increase in knowledge and safety for correct management, where 51.6% started to feel able to perform dental replantation. Conclusion: There was insufficient knowledge, mainly in the public network. However, there was an improvement in the rates after training, showing the importance of multidisciplinary work between dentists and educators.